Reinventing the post-disaster cultural landscape of heritage tourism in Kotagede, Yogyakarta, Indonesia. Issue 2 (4th March 2021) - Rindrasih, Erda; Witte, Patrick
ABSTRACT: When a disaster destroys historical buildings, it is a challenge to maintain the authenticity and originality of the buildings as a heritage tourism site, and their destruction impacts the local community, whose economy is dependent on this heritage. This paper discusses the reinventing of heritage tourism, using the case of Kotagede, Yogyakarta, which was hit by a 5.5 magnitude earthquake in 2006. The paper shows that the earthquake has refreshed the cultural landscape, and that new tourism packages using the story of heritage in combination with the earthquake event have also led to new economic opportunities. We show that the process of reinventing the post-disaster heritage tourism was however challenged by the problems of administrative versus cultural boundaries, confusing criteria concerning heritage products, conflicts in the building restoration process, a lack of interest among younger generations in culture and tradition, and unsustainable government programmes. Based on this, it can be concluded that the overlapping of the post-disaster recovery process with the reinvention of heritage tourism products may permanently change the authenticity of the cultural landscape and lead to a shift from organic place-making to planned placemaking processes.